Microbial diversity in earthen site of exhibition Hall of pit no. 1 at the terracotta warriors Museum in Emperor Qinshihuang’s mausoleum site museum and its correlation with environmental factors - Wang, Cen; Hou, Lilong; Jiang, Nan; Wang, Yu; Mao, Xiaofen; Zhou, Ping; Xia, Yin; Wang, Yuanyuan; Chen, Chuyue; Yang, Xinyu; Luo, Qiang; Pan, Jiao (Frontiers in Microbiology, 2024)
Introduction Earthen sites are essential cultural relic resources, and site museums are a fundamental component of China’s cultural heritage protection. The mausoleum of the Qin Shi Huang Emperor is one of the largest, most peculiar, and richest imperial tombs in the world. The exhibition hall of the burial pit No. 1 of the Terra Cotta Warriors is the earliest exhibition hall built and opened to the public. However, after years of excavation and open exhibitions, the earthen site of the Emperor Qinshihuang’s Mausoleum Site Museum has deteriorated to varying degrees due to changes in the modern environment. There is an urgent need to control microbial diseases and protect the earthen site. Methods We analyzed the physical and chemical properties and bioindicators of the collected soil samples. We also established a metagenomic library and conducted a correlation analysis between microbial community composition and environmental factors. Cultivable fungi obtained from air and soil samples were identified, and allicin volatile gas fungistasis test was conducted. Result Research has found that four different areas of the exhibition hall have different types of microbial diseases owing to their different environments. The main pathogenic fungi in earthen site may lead to potential microbial diseases that affect important cultural relics such as the Terra Cotta Warriors. Penicillium, Aspergillus and Talaromyces showed relatively specific growth in relation to environmental factors and showed a better raw growth advantage.Allicin gas had a inhibitory effect on 12 types of fungi, therefore allicin gas had a potent inhibitory effect on the growth of the most culturable fungal hyphae. Discussion This study provides basic data for the study of microbial diversity in the exhibition hall of Pit No. 1 at the Terracotta Warriors Museum in Emperor Qinshihuang’s Mausoleum Site Museum. It provides a reference for future protection work, which is of great significance.